A proximity proteomics screen in three-dimensional spheroid cultures identifies novel regulators of lumen formation - Li-Ting Wang (Nature Portfolio, 2021)
Abstract Apical-basal cell polarity and lumen formation are essential features of many epithelial tissues, which are disrupted in diseases like cancer. Here, we describe a proteomics-based screen to identify proteins involved in lumen formation in three-dimensional spheroid cultures. We established a suspension-based culture method suitable for generating polarized cysts in sufficient quantities for proteomic analysis. Using this approach, we identified several known and unknown proteins proximally associated with PAR6B, an apical protein involved in lumen formation. Functional analyses of candidates identified PARD3B (a homolog of PARD3), RALB, and HRNR as regulators of lumen formation. We also identified PTPN14 as a component of the Par-complex that is required for fidelity of apical-basal polarity. Cells transformed with KRASG12V exhibit lumen collapse/filling concomitant with disruption of the Par-complex and down-regulation of PTPN14. Enforced expression of PTPN14 maintained the lumen and restricted the transformed phenotype in KRASG12V-expressing cells. This represents an applicable approach to explore protein–protein interactions in three-dimensional culture and to identify proteins important for lumen maintenance in normal and oncogene-expressing cells.